Impact of rural out-migration on poverty of households in southern Ethiopia - Fassil Eshetu; Jema Haji; Mengistu Ketema; Abule Mehare (Cogent Economics & Finance, 2023)
This study examined the impact of rural out-migration on the poverty of migrant-sending households by applying the new economics labor migration theory as a theoretical framework, and the multinomial endogenous switching regression as an analytical model in southern Ethiopia. Data were gathered from 415 sample rural households using stratified random sampling in the year 2021. The cost of basic needs approach and the Foster, Greer, and Thorbecke (FGT) method were used to establish the poverty line and create the poverty indices, respectively. The average annual food and non-food poverty lines are Birr 8997.52 and 2249.38 per adult equivalent. The incidence, depth, and severity of general poverty are 39.76, 10.11, and 3.55%, respectively, while the incidence, depth, and severity of food poverty are 34.70, 9.47, and 3.58%, respectively. When compared to other households, households with international migrants have a lower incidence, depth, and severity of poverty. The regression result of the multinomial endogenous switching model showed that international migration increases consumption per adult equivalent of households by 29.8% and is significant at the 1% level. Participation in rural-urban and international migration increases kilocalories per adult equivalent per day by 7.4 and 36.4%, respectively, in migrant-sending rural households. The findings support the new economics labor migration theory's remittance hypothesis. Promoting access to land, capital, farm and non-farm employment, irrigation, family planning, and basic public services would improve rural household welfare and reduce the current wave of rural out-migration in Southern Ethiopia.
Keywords: 330; cost of basic need; Ethiopia; migration; rural poverty; switching regression